Students' perception of the auditing profession in Vietnam: The effect of proximity and knowledge on auditors' stereotype - Ngoc Tran Thanh Thuy; Dung Truong Thi Hanh; Minh Ho Thi Hong (Cogent Business & Management, 2022)
The purpose of this study was to determine the relationship between the proximity, knowledge as well as the source of knowledge about the profession and students' perception of the auditing profession in Vietnam. The data is collected using quantitative techniques based on a questionnaire survey of a total of 221 undergraduate students in Vietnam. Then the data is processed by SPSS software to determine the relationship between the factors. The results indicate that the students' main source of knowledge about the auditing profession is their academic training. Students perceive that the auditing profession is quite an interesting job with many professional development opportunities, many tasks and significant contributions to society, and they also consider auditing as a strict job and responsibility demanding. The findings also reveal that auditors are regarded as competent and high ethical. This study adds empirical information to the scientific literature in order to gain a better understanding of the impact and significance of closeness to the profession, knowledge, and sources of knowledge on students' perceptions of auditing. The study's practical implication is that having more information about a profession improves students' views of that profession.
Keywords: M40; M41; 650; stereotype; knowledge; auditor's stereotype; proximity